Convictions of conscience : how voices from the margins inform public actions and educational leadership - McMahon, Brenda J.; Merriweather, Lisa R. (Issues in the research, theory, policy, and practice of urban education., 2019)
"Convictions of conscience: How voices from the margins inform public actions and educational leadership seeks to help educational leaders to develop the competencies and capacities required to create socially just and equitable schools. It is for educational leaders interested in transforming systems and decolonizing education rooted socially, structurally and ideologically in hegemony. This edited volume promotes the questioning of assumptions embedded in neoliberal new managerialism practices that often undergird the preparation and training of school leaders. New managerialism in higher education seeks to understand the market forces in order to cater to the idiosyncratic, often self-promoting needs and interests of the few and seeks to respond with programs and policies aligned with those forces and interest. This volume suggests that the confluence of context, theory and pedagogical strategies within the field of educational leadership should inform curricular decisions in educational leadership preparation programs and such programs should be designed to prepare school leaders as both activists and advocates for marginalized students, parents, communities, and staff. Convictions of Conscience is a call on educational leaders who are committed to success for all students to reject new managerial approaches at all levels of educational leadership and is an invitation to expand their emphasis to concerns rooted in human context, particularly identity politics. Towards this end a decolonizing philosophically grounded practice of educational leadership that disrupts static relations within the structures of power is required to move toward a more socially just praxis, The chapter authors sought to problematize understandings of diversity and inclusion by emphasizing the integral role of equity and social justice as critical dimensions of human relationships. Additionally chapter authors intentionally interrogated the socio-cultural dimensions that affect educational leaders. The hope is that Convictions of conscience will be a catalyst for educational leaders to examine theory and practice and develop a discourse wherein the mediating impacts of macro and micro contexts between and among conceptions of social justice can be unmasked"--